The ion energy in a plasma resonator excited by a powerful microwave pulse at ECR frequency - Antonov, A.N.; Antipov, V.S.; Kornilov, E.A.; Miroshnichenko, V.A.; Vinokurov, V.A. (Вопросы атомной науки и техники, 2020)
The possibility of heating argon plasma ions with a density of ≈10¹³ cm⁻³ to 2 keV in a resonator placed in a magnetic field of a plug configuration when oscillations were excited at an electron-cyclotron resonance frequency with an electric field strength of up to 12 kV/cm in a pulse with a duration of 1.8 μs was shown experimentally. Ions acquire high energy in the fields of stochastic low-frequency ion oscillations due to the development of a modified decay of microwave oscillations. Експериментально показана можливість нагріву іонів аргонової плазми щільністю ≈10¹³ см⁻³ до 2 кеВ у резонаторі, розміщеному в магнітному полі пасткової конфігурації, при порушенні коливань на частоті електронно-циклотронного резонансу і напруженості електричного поля до 12 кВ/см в імпульсі тривалістю 1,8 мкс. Іони набувають високу енергію в полях стохастичних низькочастотних іонних коливань, обумовлених розвитком модифікованого розпаду НВЧ-коливань. Экспериментально показана возможность нагрева ионов аргоновой плазмы плотностью ≈10¹³ см⁻³ до 2 кэВ в резонаторе, размещенном в магнитном поле пробочной конфигурации, при возбуждении колебаний на частоте электронно-циклотронного резонанса и напряженности электрического поля до 12 кВ/см в импульсе длительностью 1,8 мкс. Ионы приобретают высокую энергию в полях стохастических низкочастотных ионных колебаний, обусловленных развитием модифицированного распада СВЧ-колебаний.